Relevant Problems of Legal Regulation of IT Modernization of Local Self-Government Technologies in Russia - SOLOVEV, Sergey Gennadevich; KIREEV, Valeriy Vitalievich; SOTNIKOVA, Liliya Vladimirovna (Journal of Advanced Research in Law and Economics, 2019)
The research is devoted to understanding the problematic issues of the regulation of the IT modernization of traditional local self-government technologies in Russia. The key theoretical and practical problems related to the content and procedural aspects of the regulation of the introduction of e-democracy forms at the municipal level have been considered. A set of legal measures aimed at improving the content of the analyzed legal structures has been proposed.